Self-textualization in Goran's poems - عەزیز, سامان جەلال (Sulaimani Journal for Humanities, 2019)
This research deals with “Groans poem”, especially self-intertextuality in his poems, which they depict his cultural and intellectual thoughts and they are nets from a lot of codes. This is direct reason for other texts associations by the mean of arouse previous poems either directly or indirectly in a new way. They are reproducing the former poems in a new artistic function not as repetition. The thesis consists of five chapters: Chapter one: It specified for intertextualitys history and its types which depends on kristivas method.Chapter two: it dealt with similarity some titles of some poems. It entitled:”self –intertextuality among titles .” Chapter three: It is entitled” Self-intertextuality by Repetitions of the same: Words, Phrases, and Sentences”. It is divided into three topics. The first topic entitled” Self-intertextuality by Repetitions of the same words”. The second topic entitled” Self-intertextuality by Repetitions of the same phrases”. The third topic entitled “Self-intertextuality by Repetitions of the same sentences.” Chapter four: this chapter deals with those poems that they have the same ideas or themes which are entitled:” Self-intertextuality by Repetitions of the same theme.” Chapter five: this chapter deals with those poems that they have the same images which are entitled:” Self-intertextuality by Repetitions of the same image”. At the end in conclusion, we show all the main conclusions which are resulted from the research.